Eye-tracking to examine differences in alcohol product appeal by sex among young people. (2nd November 2022) - Rossheim, Matthew E.; Peterson, Matthew S.; Livingston, M. Doug; Dunlap, Phenesse; Trangenstein, Pamela J.; Tran, Katherine; Emechebe, Ogechi C.; McDonald, Kayla K.; Treffers, Ryan D.; Jernigan, David H.; Thombs, Dennis L.
ABSTRACT: Background: Advertising of traditional alcopops contains elements that appeal to youth, especially females. Supersized alcopops are marketed differently than traditional alcopops and contain up to 5.5 standard alcoholic drinks. Young females are more likely to underestimate the alcohol content of supersized alcopops, putting them at higher risk of overconsumption. Similar to supersized alcopops, beer is packaged in large cans and in the same areas of store shelves. Objective: This study examined among young people whether supersized alcopops versus beer products disproportionately appealed to females. Methods: Eleven adolescents (13–17 years old) and 72 college students (21–26 years old) were recruited during 2019–2020. Participants viewed 19 photos of convenience store display cases containing both supersized alcopop and beer products. While viewing each image, participants were instructed to click on the beverage that looked the "coolest" (i.e. most appealing). Eye-tracking hardware and software measured the amount of time participants visually fixated on each product. Participants completed a survey to record demographic characteristics. Results: Compared to males (n=25), females (n=58) fixated on supersized alcopops for 6.8 seconds longer (95%CI 0.3, 13.3). Females also had 3.7 times the odds of selecting a supersized alcopop as the product they found most appealing compared to males (95%CI 1.68, 8.01), adjusting for amount of time visually fixating on supersized alcopops, which was also a significant predictor. Conclusions: Young females' strong preference for supersized alcopops is concerning given they disproportionately underestimate their potency, relative to males, and are more likely to obtain dangerously high BAC levels from consuming one or two supersized alcopops.